Understanding The Learning Process to Effectively Differentiate Instruction - Арчабаева, Наргиза (Maktabgacha taʼlim jurnali, 2022)
The underlying ability a teacher must have to orchestrate differentiated instruction day after day, hour after hour, by assessing his/her students and adjusting strategies and tactics moment by moment, requires sophisticated knowledge and skills.